KAJIAN ASPEK STUDI PERILAKU DALAM PENGAMBILAN KEPUTUSAN INVESTASI - Andreas Kiky (STIE Wiyatamandala, 2019)
Challenge to find the best stock has been very big question in investing strategy. For the investor, fund manager or financial planner portfolio selection process is the most difficult part of the investing strategy. Investors face many lists of the stocks that should be choosen and wait the price appreciation in order to gain capital-gain or dividend. The selection process has been the debate for most of investor and common mistake that always happen is heuristic bias. Sometimes investors choose the stocks just base on the pure intict or market reaction rather than the fundamental information of the firm performance. Speculative goal and instinct to grab fast capital gain causes the bias in decision making. This research wants to observe the stock ticker fluency name effect on stocks value and trading volume. This research takes 45 stocks as the sample base on LQ-45 Index.